THE STRUCTURE OF THE TRAINING COURSE «THEORY AND METHODOLOGY OF HIGH-PERFORMANCE SPORTS» IN THE MOODLE SYSTEM - Vorona, V. V. (Rehabilitation and Recreation, 2022)
Successful implementation of training courses in the Moodle distance learning system requires their constant updating and improvement. The validity of the structure and content of training courses and modernization of teaching tools corresponds to the modern educational needs of students. The goal is to justify the structure of the training course «Theory and methodology of high-performance sports» for implementation in the Moodle system of Sumy State Pedagogical University named A.S. Makarenko. The research methods have been used by the author: analysis of scientific and methodical literature, the method of expert evaluations. Twelve respondents with experience of 6-14 years in scientific and pedagogical work at Sumy State Pedagogical University named after A.S. Makarenko participated as experts in the research. The results. The works of leading specialists in the field of physical culture and sports regarding the development and presentation of educational courses in the Moodle system have been considered. Differences in the structure and content of distance learning courses have been revealed. Two versions of the distance course structure of the academic discipline «Theory and Methodology of high-performance sports» have been developed. An expert evaluation of the proposed options has been carried out and the feasibility of their use has been determined. According to the obtained results, the structure of the outlined course in the Moodle system, as stated by the experts is more convenient for use by both students and lecturers, should consist of a general block, thematic blocks with separate types of educational activities in each block (lectures, practical, independent work), a final control block. It has been found that when structuring a course in the Moodle system, it is advisable to take into account the focus of the course (theoretical or practical). Conclusions. According to the results of the expert evaluation, important structural elements necessary for ease of use and assimilation of the course knowledge by students have been highlighted. The structure of a training course in the Moodle system for higher education applicants should be clear, scientifically based and corresponds to the modern educational needs of students.